Períodos de instabilidade e gerenciamento de resultados no Brasil uma análise empírica do período do impeachment presidencial de 2016 - Andrade, Douglas Santos de (2020)
The general objective of the present study is to investigate the practice of managing results by Brazilian companies during the presidential impeachment event 2016. The study sample includes companies listed in Brazil, Bolsa, Balcão (B3) - analysis group - and, for comparative purposes, the companies of the Bolsa Mexicana de Valores (BMV) - control group. The companies' quarterly financial data were collected at datastream® database, covering the period from 2013 to 2018. To assess the robustness of results, absolute discretionary accruals (proxy for results) were measured using five alternative models: the Jones model modified (DECHOW; SLOAN; SWEENEY, 1995); the Kothari model (KOTHARI; LEONE; WASLEY, 2005); the Lacker model (LACKER; RICHARDSON, 2004); the model Dechow (DECHOW; HUTTON; KIM; SLOAN, 2012); and a consolidated model. Was the data analysis methodology used in an unbalanced panel, using the Ordinary Least Squares (OLS) estimator to estimate the coefficients. When analyzing only Brazilian companies, the results show a relationship inversely proportional between the impeachment event and the practice of managing results by accruals, indicating that Brazilian companies tend to reduce the levels of accruals in the period of impeachment. When Mexican companies are included for comparison, this trend continues, according to the significance of the beta β3 of interaction between the impeachment variables and Brazilian companies (IMPEACH x BRASILit), also in two of the models analyzed, suggesting that this tendency to decrease accruals absolute discretion was higher in Brazilian companies than in Mexican companies. Or In other words, Brazilian companies seem more concerned with not increasing levels of absolute discretionary accruals during the presidential impeachment period, possibly with incentives to take advantage of the unstable period to release guilt for a result “Bad”, that is, a method of “cleaning the house”. Consequently, the market, realizing the poor corporate performance tends to accept lower profits and more losses. It is noteworthy, in However, these results were found in only two of the models analyzed, indicating that the results of this study are relatively sensitive to the models used to measure absolute discretionary accruals.